2009
DOI: 10.1007/s00018-009-0194-0
|View full text |Cite
|
Sign up to set email alerts
|

Lucifensin, the long-sought antimicrobial factor of medicinal maggots of the blowfly Lucilia sericata

Abstract: A novel homologue of insect defensin designated lucifensin (Lucilia defensin) was purified from the extracts of various tissues (gut, salivary glands, fat body, haemolymph) of green bottle fly (Lucilia sericata) larvae and from their excretions/secretions. The primary sequence of this peptide of 40 residues and three intramolecular disulfide bridges was determined by ESI-QTOF mass spectrometry and Edman degradation and is very similar to that of sapecin and other dipteran defensins. We assume that lucifensin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 24 publications
4
75
2
1
Order By: Relevance
“…[16] Later, the production of recombinant peptide resulting in a few milligrams of active peptide was reported by Andersen. [17] Although, numerous synthetic studies in the expanding field of defensins have been published during the last two decades, only a few of these papers report the synthesis of insect defensins.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[16] Later, the production of recombinant peptide resulting in a few milligrams of active peptide was reported by Andersen. [17] Although, numerous synthetic studies in the expanding field of defensins have been published during the last two decades, only a few of these papers report the synthesis of insect defensins.…”
Section: Discussionmentioning
confidence: 98%
“…We supposed that the three-dimensional structure of lucifensin is similar to that of sapecin, [30] because the primary sequence of sapecin (40 residues) differs from the sequence of lucifensin by only four amino acid residues (Ile11, Asn12, Lys33, Val35). The conformation of sapecin was determined by 1 H NMR spectroscopy and simulated annealing calculations, [30] resulting in a structure that includes an N-terminal flexible loop (residues 4-12), a helical part (residues [15][16][17][18][19][20][21][22][23], and an antiparallel b-structure (residues 24-31 and 34-40). Significant antimicrobial activity of the Luc[C16-C36] analogue against the most sensitive bacterium M. luteus (Figure 7 A) in comparison with the other two analogues containing one disulfide bridge clearly indicates that the disulfide bond between Cys16 and Cys36, which connects the 15-23 helical part of the molecule with the 34-40 strand is the most important one for maintaining the ordered structure of lucifensin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic effects include the removal of necrotic tissue (debridement), the acceleration of wound healing, and wound disinfection (5,6). The wound disinfection property has been attributed to antimicrobial components in the larval secretions, including small molecules with antibacterial activity (7,8) and antimicrobial peptides (AMPs), such as the defensin-like lucifensin (9) and a recently reported AMP with potent antifungal activity, which accordingly was named lucimycin (10).…”
mentioning
confidence: 99%
“…Lucifensin was first purified in 2010 from an extract of the gut of L. sericacta larvae by Čeřovský et al [142]. They showed that the peptide contained 40 amino acid residues and 3 disulphide bridges and was a typical 4 kDa dipteran defensin.…”
Section: Maggot Moleculesmentioning
confidence: 99%